Changes in cardiac output with hemodialysis relate to net volume balance and to inferior vena cava ultrasound collapsibility in critically ill patients. Issue 1 (1st January 2020) - Kaptein, Matthew J.; Kaptein, John S.; Nguyen, Christopher D.; Oo, Zayar; Thwe, Phyu Phyu; Thu, Myint Bo; Kaptein, Elaine M.
Abstract: Cardiac output may increase after volume administration with relative intravascular volume depletion, or after ultrafiltration (UF) with relative intravascular volume overload. Assessing relative intravascular volume using respiratory/ventilatory changes in inferior vena cava (IVC) diameters may guide volume management to optimize cardiac output in critically ill patients requiring hemodialysis (HD) and/or UF. We retrospectively studied 22 critically ill patients having relative intravascular volume assessed by IVC Collapsibility Index (IVC CI) = (IVCmax-IVCmin)/IVCmax*100%, within 24 h of cardiac output measurement, during 37 intermittent and 21 continuous HD encounters. Cardiac output increase >10% was considered significant. Net volume changes between cardiac outputs were estimated from "isonatremic volume equivalent" (0.9% saline) gains and losses. Cardiac output increased >10% in 15 of 42 encounters with IVC CI <20% after net volume removal, and in 1 of 16 encounters with IVC CI ≥20% after net volume administration ( p = 0.0136). All intermittent and continuous HD encounters resulted in intradialytic hypotension. Net volume changes between cardiac output measurements were significantly less (median +1.0 mL/kg) with intractable hypotension or vasopressor initiation, and net volume removal was larger (median −22.9 mL/kg) with less severe intradialytic hypotension ( p < 0.001). Cardiac output increased >10% more frequently with least severe intradialytic hypotension and decreased with most severe intradialytic hypotension ( p = 0.047). In summary, cardiac output may increase with net volume removal by ultrafiltration in some critically ill patients with relative intravascular volume overload assessed by IVC collapsibility. Severe intradialytic hypotension may limit volume removal with ultrafiltration, rather than larger volume removal causing severe intradialytic hypotension.